Assessment of HIV transfusion transmission risk in South Africa: a 10‐year analysis following implementation of individual donation nucleic acid amplification technology testing and donor demographics eligibility changes. Issue 1 (28th September 2018) - Vermeulen, Marion; Lelie, Nico; Coleman, Charl; Sykes, Wendy; Jacobs, Genevieve; Swanevelder, Ronel; Busch, Michael; van Zyl, Gert; Grebe, Eduard; Welte, Alex; Reddy, Ravi
Abstract : BACKGROUND: In 1998 we estimated that 34/million infectious window period donations were entering the blood supply at the South African National Blood Service. Selective use of donations based on donor race‐ethnicity reduced this risk to 26/million donations but was deemed unethical. Consequently, in 2005 South African National Blood Service eliminated race‐ethnicity–based collection policies and implemented individual‐donation nucleic acid testing (ID‐NAT). We describe the change in donor base demographics, human immunodeficiency virus (HIV) detection rates, and transfusion‐transmissible HIV risk. STUDY DESIGN AND METHODS: In ten years 7.7 million donations were tested for anti‐HIV and HIV RNA. Number of donations, HIV prevalence, ID‐NAT yield rate, serology yield rate and residual transfusion‐transmissible HIV risk were analyzed by donor type, race‐ethnicity, age, and sex. Multiple regression analysis was performed to investigate the determinants of HIV‐positive and nucleic acid testing yield donations. RESULTS: The combined strategy of increasing donations from black donors and implementing ID‐NAT increased the proportion of donations from black donors from 6% in 2005 to 30% in 2015 (p < 0.00001), and reduced the transfusion‐transmissible risk from 24 to 13 per million transfusions. ID‐NAT interdicted 481 (1:16, 100) seronegative window period donations, while one transfusion‐transmissible case (0.13 per million) was documented. Race‐ethnicity and donor type were highly significant predictors of HIV positivity, with adjusted odds ratio for first‐time donors of 12.5 (95% confidence interval, 11.9‐13.1) and for black race‐ethnicity of 31.1 (95% confidence interval, 28.9‐33.4). The proportion of serology yields among HIV‐infected donors increased from 0.27% to 2.4%. CONCLUSION: ID‐NAT enabled the South African National Blood Service to increase the number of donations from black donors fivefold while enhancing the safety of the blood supply. Abstract : See article on page 9–11, in this issue